Habitus of Culture: Retaining Batik’s Identity amidst the Modernization - Kamsidjo Budi Utomo (Universal Journal, 2020)
Amidst the rapid modernization, Batik is now considered old-fashioned and less favored; as an icon of traditional textile art, Batik has been inferior in keeping up with current demands of a so-called “modern” society. The quick-spreading fad of kekinian (or „trendy‟, „hype‟) has been more familiar to the younger generation. This phenomenon calls for a critical outlook on the “metaphysics of presence” that lays its foundation on the principle of aesthetics. To this growing lifestyle, perfections in life are achieved by expediency and pragmatism. Contrary to that, batik offers traditionalistic, symbolic approach of representing meaning; therefore, it becomes less popular compared to the recent trends. This study, however, sees the relevance of raising the discourse of batik in the midst of recent trends by approaching it from the lens of cultural pluralism that highlights its emphasis on a nation‟s “character”. However, in lieu of mere attempt of “reviving” the relevance of batik, this study aims further to discuss batik‟s true nature and the development of its existence throughout the advancement of culture and science.